Genetic evolution, epidemic trends, and recombination dynamics of PRRSV-1 in China - Weng, Chengzhen; Huang, Xinxin; Chen, Zhian; He, Minjia; Zhang, Beiwen; Li, Hongxi; Xie, Jingrui; Chen, Meichun; Qiu, Longxin; Li, Xiaobing; Cao, Chong; Chen, Hongbo (Frontiers in Veterinary Science, 2025)
The persistent threat of porcine reproductive and respiratory syndrome virus (PRRSV) to the global swine industry is exacerbated by the virus’s high mutation rate and frequent recombination events. In China, the emergence of new PRRSV-1 strains in recent years has posed a significant challenge to the sustainability of pork production. This study systematically investigated the epidemiological patterns, genetic evolution, recombination dynamics, GP5 genetic diversity, and N-glycosylation variants of PRRSV-1 strains circulating in China. Whole-genome analysis demonstrated that Chinese PRRSV-1 isolates clustered within subtype 1, with BJEU06-1-like as the predominant subgroup and NMEU09-1-like as the secondary subgroup. Novel subgroups (new subgroups 1, 2, and 3), a new strain, GD2022, and an independent branch represented by strain GXFS20220129 were concurrently identified. High genetic diversity existed both within and between subgroups of Chinese PRRSV-1 strains. Whole-genome recombination has predominantly occurred through inter-subgroup exchange, primarily involving the BJEU06-1-like and Amervac-like lineages. Additionally, recombination events were identified between the field strain NVDC-FJ and the vaccine strain PRRSV1-CN-FJFQ-1-2023. Interestingly, the diversity of the ORF5 gene was consistent with that of the whole genome; however, there is a deviation in the phylogenetic tree position (BJEU06-1-like: 22 vs. 16). To understand the differences between ORF5 and whole-genome variations, we analyzed amino acid and glycosylation sites of the GP5 protein encoded by ORF5. The results indicated that mutations had occurred at amino acid sites within the antigenic epitopes and functional domains of GP5. Additionally, the prediction of potential N-glycosylation sites identified five locations in GP5: positions 35, 37, 38, 46, and 53. Alterations at these sites could facilitate immune evasion. Our analysis of the ORF5 gene suggests that PRRSV-1 research should not focus solely on ORF5 but rather must consider whole-genome variation, as this may provide insights for vaccine development. In summary, whole-genome studies of PRRSV-1 demonstrated that major recombinant subgroups and genetic evolution align with the current prevalence of BJEU06-1-like strains in China. Analysis of GP5 encoded by ORF5 confirmed the presence of differences between whole-genome and ORF5 data, exhibiting minor discrepancies in both the phylogenetic trees and the level of genetic diversity. Thus, instead of focusing solely on specific regions, whole-genome studies are needed to effectively track variation in PRRSV. This study fills a knowledge gap in our understanding of the prevalence and genetic variation of PRRSV-1 in China, providing crucial insights for developing PRRS control strategies and offering theoretical support for vaccine development.